2009
DOI: 10.1007/s10571-008-9328-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dopamine D1 and D2 Receptor Gene Expression in the Hippocampus of Hypoglycaemic and Diabetic Rats

Abstract: Hypoglycaemic coma and brain injury are potential complications of insulin therapy. Hippocampal neurons are particularly vulnerable to hypoglycaemic stress leading to memory impairment. In the present article, we have investigated the dopamine (DA) content, homovanillic acid (HVA)/DA turnover ratio, DA D(1) and DA D(2) receptors in the hippocampus of insulin-induced hypoglycaemic (IIH) and streptozotocin induced diabetic rats where brain functions are impaired. The DA content decreased significantly in hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 72 publications
3
15
1
1
Order By: Relevance
“…We found that DopR1 and dilp2-3, 5 mutants share night phenotypes and that rapamycin did not affect sleep of DopR1 mutants, suggesting that TOR acts on dopaminergic signalling to affect night sleep. Reduced IIS elevated expression of DopR1 , independently of dFOXO, in accordance with data from mammals [63]. This effect may be feedback caused by down-regulation of dopaminergic signalling in IIS mutants, although not through direct regulation of DopR.…”
Section: Discussionsupporting
confidence: 88%
“…We found that DopR1 and dilp2-3, 5 mutants share night phenotypes and that rapamycin did not affect sleep of DopR1 mutants, suggesting that TOR acts on dopaminergic signalling to affect night sleep. Reduced IIS elevated expression of DopR1 , independently of dFOXO, in accordance with data from mammals [63]. This effect may be feedback caused by down-regulation of dopaminergic signalling in IIS mutants, although not through direct regulation of DopR.…”
Section: Discussionsupporting
confidence: 88%
“…This might be due to enhanced expression of D 2 -dopamine receptors or to the changes of their binding characteristics, which compensates for a decreased level of G i protein expression and maintains the efficiency of bromocryptine-induced signaling at the level similar to that in control. This suggestion finds confirmation in the recent investigation showing that the B max of a total dopamine receptor binding and the expression of D 1 -and D 2 -dopamine receptors in the cerebral cortex of rats with streptozotocin DM are increased [36,37].…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies from our laboratory, have reported the altered neurotransmitter receptor status during diabetes, was brought back to normal during optimal dosage of insulin therapy whereby increased blood glucose level during diabetes is brought back to near normal (Gireesh et al 2008). Glutamatergic and dopaminergic receptor functional deficit associated with hypoglycemia and diabetic hyperglycemia (Robinson et al 2009) and cholinergic neuronal dysfunction in the cerebellar region is reported in our previous research (Antony et al 2010).…”
Section: Discussionmentioning
confidence: 56%